The role of extracellular matrix in angiogenesis: Beyond adhesion and structure - Jaxson R. Libby; Haley Royce; Sarah R. Walker; Linqing Li (Biomaterials and Biosystems, 2024)
While the extracellular matrix (ECM) has long been recognized for its structural contributions, anchoring cells for adhesion, providing mechanical support, and maintaining tissue integrity, recent efforts have elucidated its dynamic, reciprocal, and diverse properties on angiogenesis. The ECM modulates angiogenic signaling and mechanical transduction, influences the extent and degree of receptor activation, controls cellular behaviors, and serves as a reservoir for bioactive macromolecules. Collectively, these factors guide the formation, maturation, and stabilization of a functional vascular network. This review aims to shed light on the versatile roles of the ECM in angiogenesis, transcending its traditional functions as a mere structural material. We will explore its engagement and synergy in signaling modulation, interactions with various angiogenic factors, and highlight its importance in both health and disease. By capturing the essence of the ECM's diverse functionalities, we highlight the significance in the broader context of vascular biology, enabling the design of novel biomaterials to engineer vascularized tissues and their potential therapeutic implications.